PROBLEMATIKA PENGELOLAAN DAN PENGEMBANGAN POTENSI WAKAF UANG DI DUSUN TAMBUNG BATUE, DESA BAROMBONG, KECAMATAN GANTARANG, KABUPATEN BULUKUMBA - Trisno Wardy Putra; Ainun Musfira (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2021)
Waqf is one of the Islamic economic instruments that can be used as an instrument in development. In addition, waqf also improves community welfare if it is managed properly and productively. With the possibility of developing waqf in Indonesia considering that Indonesian society is actually the largest Muslim population, it is fitting that we train and develop waqf for the welfare of the ummah. This research was conducted to find and solve problems in terms of management and development of the potential for waqf in Gantarang District, which is one of the largest sub-districts in Bulukumba Regency, but the management and development of waqf is still very minimal. The type of research used in this research is qualitative research where descriptive data is obtained in the form of the words or behavior of the people being observed. The results showed that the management and development of the potential for waqf in Gantarang District, Bulukumba Regency was still low and still not productive. For this reason, special attention is needed from the government, especially the District KUA (Office of Religious Affairs) as an extension of the BWI (Indonesian Waqf Board) in order to further improve performance and expand community socialization about waqf.